CO2 methanation in a bench-scale bubbling fluidized bed reactor using Ni-based catalyst and its exothermic heat transfer analysis. (1st January 2021) - Nam, Hyungseok; Kim, Jung Hwan; Kim, Hana; Kim, Min Jae; Jeon, Sang-Goo; Jin, Gyoung-Tae; Won, Yooseob; Hwang, Byung Wook; Lee, Seung-Yong; Baek, Jeom-In; Lee, Doyeon; Seo, Myung Won; et al.
Abstract: CO2 methanation, as a power-to-gas technology, is considered to be an important method to secure energy supply by utilizing CO2 and H2 gases. In this study, a 0.2 kW CH4 bench-scale fluidized bed reactor was used for CO2 methanation using approximately 13 kg nickel-based catalyst to investigate the effect of temperature, gas velocity, and H2 /CO2 ratio on CO2 conversion, CH4 purity, and CH4 selectivity. Response surface methodology (RSM) was employed to design the experimental conditions to statistically evaluate the effect of operating variables. Reduced quadratic model equations for CO2 conversion and CH4 purity were derived, which determined the optimal conditions within the experimental conditions. The suggested conditions for the highest CO2 conversion were 297 °C, 4.66H2 /CO2, and 4.0 Ug /Umf (velocity ratio), whereas different conditions were determined for the highest CH4 purity. Among the operating variables, temperature was the most influential factor, followed by the gas ratio. The highest CO2 conversion and CH4 purity were 98% and 81.6%, respectively. Additionally, the heat transfer coefficient (ho ) was found to be 115 W/m 2 ∙°C during a 10-h continuous CO2 methanation experiment, which is an important design factor for the further scale-up of the process. Highlights: CO2 methanation was performed in a fluidized bed reactor using nickel beads. CO2 conversion and CH4 purity were 98% and 81%, respectively. Optimal conditions for CO2 conversion were 297 °C, 4.6H2 /CO2 and 4 Ug /Umf . Heat transfer coefficient during CO2 methanation was 115 W/m 2 / o C.